Gene farináceo-2 afetando características físicas e químicas de milhos tropicais - de Pádua Nacif , Antônio; Morais Barbosa , Hélio; Anderson, John C; Saraiva, Luiz Sérgio (Revista Ceres, 2025)
The maize mutant floury-2 (fl2) was introduced by means of four backcrosses into a flint and a dent composite to determine chemical and physical characteristics of floury-2 kernels as compared to normal kernels of the same ear. The floury-2 gene decreased kernel weight and density, and weight of degermed kernel. However, it increased percent protein in the germ and percent lysine in the degermed kernel. Percent protein in degermed was not affected by the gene. The effect of the gene on percent lysine in the germ varied with the genetic background.